Resilience and peace-building for water-related vulnerabilities in fragile and conflict-affected communities: a technical guide - Osei-Amponsah, Charity; Okem, Andrew; Onyeneke, R.; Ruckstuhl, Sandra (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2024)
Water-related vulnerabilities are increasingly contributing to tensions in fragile and conflict-affected communities (FCACs). Therefore, water development practitioners should be well-equipped to assess how their interventions can potentially reinforce vulnerabilities or support resilience and peacebuilding. The resilience-peacebuilding nexus is one of the critical entry points to addressing the complex and interconnected water-related challenges. This technical guideline aids the formulation and implementation of conflict-sensitive water-related development projects. It outlines three main steps to understanding the realities of water-related vulnerabilities and provides pathways for resolving them towards building resilience and peace. The first step focuses on the contextual analysis of the water system, including institutions, stakeholders and socio-demographic intersections. Step two is geared towards understanding the links of vulnerabilities and risks in the water system, to designing development projects in a fragile and conflict context. The third step provides a guide to mediating conflicts and building peace in the water system. The steps are important for ensuring that practitioners effectively manage challenges, generating additional risks and reinforcing water vulnerabilities to exacerbate conflicts in fragile contexts.